Non-trivial factors as determinants of the environmental taxation revenues in 27 EU countries - Concetta Castiglione; Davide Infante; Janna Smirnova (Economies, 2018)
The implementation of environmental taxation is one of the most important issues of environmental policy in Europe. To approach this matter, the paper aims to analyse the determinants of environmental taxation revenue for European countries. Besides investigating the most explored determinants, such as those related to production, consumption and environmental quality, particular attention is paid to some non-trivial factors. Firstly, we analyse the importance of the institutional context that is crucial for policy enforcement. Secondly, we consider the consumption of rapidly obsolescent goods, such as information and communication technology (ICT) goods characterised by intensive waste generation. Finally, the importation of final goods as a consequence of production offshoring is taken into account. The results demonstrate that the above-mentioned determinants have a heterogeneous impact on environmental taxation revenue in EU Western countries and EU Eastern countries, which can be due to a still weak institutional context of the latter economies and their peculiar patterns of development.
Keywords: F18; H23; O10; Q58; 330; environmental protection; institutions; ICT